Motivation, discipline, and competence: Improving employee performance at the Jayapura Regency Office - Karim, Latif; Morin, Henderina; Binur, Roland E. (Goodwood Publishing, 2025)
Purpose: This study aims to examine the influence of motivation, discipline, and competence on employee performance at the Jayapura Regency Office. Methodology/approach: The research employed a quantitative approach, involving 51 employees from various departments within the Jayapura Regency Office. Data were collected through structured surveys and analyzed using multiple regression analysis with Partial Least Squares (PLS) to assess the relationship between the independent variables (motivation, discipline, and competence) and the dependent variable (employee performance). Results/findings: The analysis revealed that motivation and discipline have significant positive effects on employee performance, with motivation showing the strongest impact. However, competence was found to have no significant direct effect on employee performance in this organizational context. Conclusion: The study concludes that motivation and discipline are critical factors in enhancing employee performance at the Jayapura Regency Office, while competence alone does not directly improve performance. These findings suggest that organizational leaders should prioritize strategies to boost employee motivation and enforce discipline, while also considering how to better leverage employee competencies through supportive work environments and systems. Limitations: A key limitation of this study is its focus on a single government office, which may restrict the generalizability of the findings to other organizational contexts. Additionally, the use of self-reported data may introduce response biases, and the cross-sectional design prevents establishing causal relationships. Contribution: This study contributes to public sector management by revealing how motivation, discipline, and competence differently affect employee performance, offering practical guidance for government institutions to improve productivity through targeted motivational, disciplinary, and competence-enabling interventions strategies.